Education, skill training, and lifelong learning in the era of technological revolution. - Kim, Jinyoung ([Manila] Asian Development Bank, 2020)
Rapid technological progress is now resulting in skills depreciation faster than it did in the past, calling for better skills management throughout workers lifetimes. Proper skill mixes for future jobs are also different from current job requirements. Findings from the studies particularly in labor and demographic economics can shed light on new directions for lifelong education policies.
Keywords: Educational innovations; Education -- Laws and legislations; Electronic book